Impact of functional groups in spacer cations on the properties of PEA-based 2D monolayer halide perovskites - Chenchen Li; Xian Chen; Tan Jin; Tianmin Wu; Jun Chen; Wei Zhuang (Nano Materials Science)
Incorporating low-dimensionalization technologies effectively tackle the challenge of inadequate long-term stability in hybrid halide perovskites, however their wide bandgap and strong quantum well confinement remain substantial obstacle for various optoelectronic applications. Addressing these issues without compromising long-term stability has emerged as a pivotal focus in materials science, in particular exploring the effects of the functional groups within spacer cations. Our simulations reveal that the robust π-π stacking interactions involving PEA+ and the strong hydrogen bonding interactions between PEA+ and MX64− contribute to narrowing the electronic bandgap in 2D monolayer PEA2MX4 (e. g. 2D monolayer PEA2SnI4: 1.34 ​eV) for reasonable visible-light absorption while simultaneously ensuring their favorable long-term stability. Moreover, the delocalized orbitals and relatively high dielectric constants in PEA+, attributed to the conjugated benzene ring, has been observed to weaken the potential barrier, exciton binding effect and quantum well confinement in 2D monolayer PEA2MX4, thus facilitating photogenerated electron-hole separations and out-of-plane carrier transport. The impact of spacer cations on the optoelectronic and transport properties of 2D monolayer perovskites highlights the critical role of meticulously chosen and well-designed spacer cations, especially functional groups, in shaping their photophysical properties and ensuring long-term stability even under extremely operating conditions.